2020
DOI: 10.1200/jco.20.00150
|View full text |Cite|
|
Sign up to set email alerts
|

Antithymocyte Globulin for Matched Sibling Donor Transplantation in Patients With Hematologic Malignancies: A Multicenter, Open-Label, Randomized Controlled Study

Abstract: PURPOSE The role of antithymocyte globulin (ATG) in preventing acute graft-versus-host disease (aGVHD) after HLA-matched sibling donor transplantation (MSDT) is still controversial. PATIENTS AND METHODS We performed a prospective, multicenter, open-label, randomized controlled trial (RCT) across 23 transplantation centers in China. Patients ages 40-60 years with standard-risk hematologic malignancies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…Recently, a prospective multicenter open-label randomized controlled clinical trial by Chang et al showed that addition of 4.5 mg/kg ATG in MSD-HSCT, sources of graft including peripheral blood and bone marrow and peripheral blood + bone marrow, could reduce not only the risk of overall cGVHD (27.9% versus 52.5%, p<0.001) and extensive cGVHD (8.5% versus 23.2%, p=0.029) but also the risk of grade 2–4 aGVHD (13.7% versus 27.0%, p=0.007). 34 However, in regard to survival and efficacy, Kröger et al and Chang et al observed no significant between-group differences in relapse, NRM, LFS or OS, while GRFS in the study of Chang et al was much better in the ATG group than that in the non-ATG group (38.7% versus 24.5%, p=0.003). In cord blood transplantation (CBT), the use of ATG may need further confirmation and exploration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, a prospective multicenter open-label randomized controlled clinical trial by Chang et al showed that addition of 4.5 mg/kg ATG in MSD-HSCT, sources of graft including peripheral blood and bone marrow and peripheral blood + bone marrow, could reduce not only the risk of overall cGVHD (27.9% versus 52.5%, p<0.001) and extensive cGVHD (8.5% versus 23.2%, p=0.029) but also the risk of grade 2–4 aGVHD (13.7% versus 27.0%, p=0.007). 34 However, in regard to survival and efficacy, Kröger et al and Chang et al observed no significant between-group differences in relapse, NRM, LFS or OS, while GRFS in the study of Chang et al was much better in the ATG group than that in the non-ATG group (38.7% versus 24.5%, p=0.003). In cord blood transplantation (CBT), the use of ATG may need further confirmation and exploration.…”
Section: Discussionmentioning
confidence: 88%
“…The risk of relapse did not increase, and the OS was effectively improved, as were LFS and GRFS, although no statistical significance was found in the univariate or multivariate analyses (Tables 6 and 7 and Figure 2A-D). We have noticed that the benefit of ATG in preventing aGVHD after MSD-HSCT was once considered controversial, 15,33 but it has been confirmed recently in the study of Chang et al 34 Considering that the transplant procedures, including conditioning regimen and GVHD prophylaxis, were almost the same in our two studies, we analyzed whether the difference in the aGVHD result might be partly due to patient age (40-60 years old), which is thought to be associated with an increased risk of aGVHD. 32 Although many studies have confirmed the protective effects of ATG, the issue is that an insufficient dose of ATG cannot exert an effective immunosuppressive function, while high-dose ATG will produce an inhibitory effect on host immune function, resulting in delayed immune reconstruction, increasing the risk of infection and relapse, and ultimately negatively affecting survival.…”
Section: Dovepressmentioning
confidence: 99%
“…The median relapse time was 2 (2-4) months after transplantation, which indicated that the early relapse was related with the preconditioning effects, but not with graft-versus-leukemia (GVL) effects. Low-dose ATG for GvHD prophylaxis in MRD transplantation did not increase the relapse risk, which has been demonstrated in several clinical trials [30][31][32]. PTCy has been demonstrated in preclinical experiments that it could separate GvHD and a GVL effect [33] and did not increase the relapse risk in clinical studies [34,35].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, strategies reducing the risk of GVHD, without reducing the GVL effect are strongly desired. A recent publication suggest antithymocyte globulin (ATG) may possess such properties, as it could reduce the risk of GVHD without compromising with increased risk for relapse [15].…”
Section: Selection Of Immunosuppressive Strategiesmentioning
confidence: 99%